Slippery fish: Enforcing regulation when agents learn and adapt - Andres Gonzalez Lira; Ahmed Mushfiq Mobarak (Yale University, Economic Growth Center, 2021)
Attempts to curb undesired behavior through regulation gets complicated when agents can adapt to circumvent enforcement. We test a model of enforcement with learning and adaptation, by auditing vendors selling illegal fish in Chile in a randomized controlled trial, and tracking them daily using mystery shoppers. Conducting audits on a predictable schedule and (counter-intuitively) at high frequency is less effective, as agents learn to take advantage of loopholes. A consumer information campaign proves to be almost as cost-effective and curbing illegal sales, and obviates the need for complex monitoring and policing. The Chilean government subsequently chooses to scale up this campaign.
Keywords: K42; O1; L51; 330; Enforcement; Regulation; Law and Economics; Fisheries